Runx2 induces osteoblast and chondrocyte differentiation and enhances their migration by coupling with PI3K-Akt signaling - Fujita, Takashi (The Rockefeller University Press, 2004)
Runx2 and phosphatidylinositol 3-kinase (PI3K)–Akt signaling play important roles in osteoblast and chondrocyte differentiation. We investigated the relationship between Runx2 and PI3K-Akt signaling. Forced expression of Runx2 enhanced osteoblastic differentiation of C3H10T1/2 and MC3T3-E1 cells and enhanced chondrogenic differentiation of ATDC5 cells, whereas these effects were blocked by treatment with IGF-I antibody or LY294002 or adenoviral introduction of dominant-negative (dn)–Akt. Forced expression of Runx2 or dn-Runx2 enhanced or inhibited cell migration, respectively, whereas the enhancement by Runx2 was abolished by treatment with LY294002 or adenoviral introduction of dn-Akt. Runx2 up-regulated PI3K subunits (p85 and p110β) and Akt, and their expression patterns were similar to that of Runx2 in growth plates. Treatment with LY294002 or introduction of dn-Akt severely diminished DNA binding of Runx2 and Runx2-dependent transcription, whereas forced expression of myrAkt enhanced them. These findings demonstrate that Runx2 and PI3K-Akt signaling are mutually dependent on each other in the regulation of osteoblast and chondrocyte differentiation and their migration.